Optimal fabrication and sintering behaviors of ferroelectric PZT/WO 3 ceramics - Jiansirisomboon S. (2014)
The research reports the results of an investigation into the effects of processing temperature and concentration of nano-sized WO3 addition on phase formation, densification and grain size of PZT ceramics. Increasing the content of WO3 addition and sintering temperature showed a complementary effect on tetragonal-to-rhombohedral phase formation. An addition of only 0.5 vol% of WO3 was found to help increase the densities as well as dramatically reduced the grain size of the PZT/WO3 ceramics regardless of sintering temperature used. Based on these results, optimum processing temperature is about 1200°C where high-density, high-purity PZT/WO3 ceramics were obtained.